The results of winter wheat breeding on grain quality in the Tatar RIA - I. D. Fadeeva; M. Sh. Tagirov; I. N. Gazizov (Зерновое хозяйство России, 2018)
The results of winter wheat breeding on grain quality in the Tatar RIA The article considers the study results of the technological and baking properties of the regional and promising varieties of winter soft wheat by the Tatar RIA. In 2011, 2013, 2016 there was a deficit of precipitations during the period of ripening. In 2012, 2014 there was an average amount of precipitations, in 2015 it exceeded the norm in 2.6 times. On average protein content in grain ranged from 13.3 to 14.1%. The index varied from 11.2 to 13.9% depending on the year. The variety ‘Nadezhda’ showed a slight variability of the trait ‘mass share of protein’ (9.1%). The coefficient of variability of the trait ‘mass share of gluten’ was 15.4% on average. The coefficient of variability of the trait ‘index of gluten deformation’ ranged from 13.2% to 21.2%. There was established a significant effect of environmental conditions on the formation of the traits ‘dough time’, ‘dough stability’ and ‘dough dilution’. Average phenotypic variability was obtained in the traits ‘valorimetric assessment’ and ‘flour strength’. The varieties ‘Universiada’ (5.7 %) and ‘Kazanskaya 560’ (8.8 %) showed a slight variability of the trait ‘flour strength’.All varieties had a slight variability of the trait ‘general baking assessment’ (from 4.1 to 9.9%). According to this index the varieties ‘Kazanskaya 285’, ‘Nadezhda’ and ‘Darina’ can be classified as strong wheat, the varieties ‘Kazanskaya 560’, ‘Universiada’ and ‘Sultan’ can be classified as valuable wheat with qualitative grain. The year conditions had a significant effect on such indexes of grain quality as mass share of protein and gluten in grain, dough dilution, valorimetric assessment, index of gluten deformation and volume yield of bread. Such indexes as ‘mass share of gluten in grain’ and ‘valorimetric assessment’ had significant genetic dependence that allows using them for selection on the improvement of grain quality in different climatic conditions.